Analisis Faktor Rendahnya Minat Belajar Bahasa Inggris Siswa SMP Negeri 18 Raja Ampat - Aulya, Annisa Fitri; Farida, Nadiyah; Hermanto (LPPM IAIN Sorong, 2023)
This research aims to determine the factors causing the low interest in learning of students at SMP Negeri 18 Raja Ampat in learning English. This research uses descriptive qualitative methods. The research subjects were 45 students in class VIII A and VIII B of SMP Negeri 18 Raja Ampat semester 1 of the 2023/2024 academic year. The data collection techniques used were observation, interviews and documentation. The results of this research consist of internal factors and external factors. Internal factors include students' perception that English is a difficult subject because memorizing a lot of vocabulary and pronunciation in English is quite complicated. External factors include parents' lack of understanding about the importance of students' academic achievement, geographical conditions that can prevent students from going to school, economic factors that make students prefer to skip school to work, and teachers' less attractive teaching methods.